Is There a Role for Medication in Managing Delirium with Dementia? - Elizabeth L. Sampson; Frederick Graham; Andrew Teodorczuk (Geriatrics, 2022)
People with dementia are more likely to develop delirium. We conducted a brief literature search and give a pragmatic overview of the key issues. Making rational and safe prescribing decisions is highly influenced by organisational culture and embedded staff practices. Comprehensive assessment for unmet physical, psychological, and social needs is an important intervention in itself. Taking a broad overview of possible pharmacological interventions should include stopping inappropriate medications and prescribing for key drivers of the underlying causes of delirium. Prescribing psychotropic medications may be indicated where there is significant distress or risk to the person with dementia and risk to those around them. It is vital to consider the dementia subtype and, where possible, involve family and friend carers in the decision-making process. Medications should be prescribed at the lowest possible dose for the least amount of time after carefully weighing risks versus benefits and documenting these. While these cases are challenging for staff and families, it can be rewarding to improve the quality of life and lessen distress for the person with dementia. There are also opportunities for informing family and friend carers, educating the wider multidisciplinary team, and promoting organisational change.